Narrow band imaging for detection of gastric intestinal metaplasia and dysplasia: A systematic review and meta‐analysis. Issue 8 (14th June 2021) - Desai, Madhav; Boregowda, Umesha; Srinivasan, Sachin; Kohli, Divyanshoo R.; Al Awadhi, Sameer; Murino, Alberto; Yu, Lawrence Ho Khek; Dinis‐Ribeiro, Doutor Mário; Sharma, Prateek
Abstract: Background and Aims: Gastric intestinal metaplasia (GIM), a precursor of gastric adenocarcinoma, is challenging to diagnose with white light endoscopy (WLE) and can be missed by random gastric biopsies. Narrowband imaging (NBI) may potentially improve the detection of GIM. However, pooled estimates from prospective studies are lacking. Methods: Electronic databases were searched for studies comparing NBI and WLE alone for detection of GIM and synchronous dysplasia. Primary outcome was pooled detection rate of GIM by NBI compared with WLE in prospective studies. The secondary outcome was concurrent dysplasia detection. Results: Ten studies were found eligible from 306 articles screened. Eight prospective studies were found eligible for primary endpoint of GIM detection. Two other retrospective studies were included for dysplasia detection. A total of 1366 subjects (694 males, 54.4 ± 5.08 years) underwent upper endoscopy. GIM was detected in 482 (35.3%) subjects. NBI detected GIM in 32% additional subjects (70% vs 38%, RR 1.79; 95% CI 1.34–2.37; P  < 0.01). Subgroup analysis revealed newer NBI scopes (GIF260) detected significantly more GIM than WLE (RR 2.47; 95% CI 1.63–3.76; P  < 0.01) but not the older (H180) NBI endoscopes (RR 1.33; 95% CI 0.93–1.88; P  = 0.11). There was moderate heterogeneity between the studies ( I 2  = 63%). In five studies ( n  = 628) that reported dysplasia, there was no significant difference between NBI and WLE in dysplasia detection (RR 1.09; 95% CI 0.81–1.47; P  = 0.58). Conclusion: Narrowband imaging can significantly increase the detection of GIM when used in addition to standard white light exam during an upper endoscopy.